A childhood citizenship? Research findings on the movement for a culture of childhood and adolescence rights in Chile - Figueroa Grenett, Claudio (Última Década, 2019)
The present article analyses the experience of boys, girls and adults in the Movement for a Culture of Childhood and Adolescence Rights born in Chile in 2008. Findings concerning oppression on children, the internal dynamics of the movement and its ways of political action are described. The article shows the production of subjectivity is relieved to a third space, suspending the social adult-centered significance and enabling a childhood citizenship.